Ekstraksi dan Uji Stabilitas Daun Teh Hijau (Camellia sinensis L.) sebagai Eye Stick Antioksidan - Jessi Eratika Putri Radian; Eny Widhia Agustin (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The eye area is the part of the face that most quickly shows signs of fatigue which is influenced by various factors. Green Tea Leaves (Camellia sinensis L.) are known as one of the plants that have high antioxidant content. The antioxidant content in green tea leaves can protect the skin from free radicals that can accelerate the appearance of signs of fatigue, including in the eye area. This study aims to develop an innovative cosmetic preparation in the form of an eye stick and determine the formula with variations in the concentration of Green Tea (Camellia sinensis L.) leaf extract that has the best antioxidant activity and good stability of the preparation. This study is an experimental study with two variations of extract concentration, namely 1% and 6%, which are obtained through an extraction process using 96% ethanol. The eye stick preparation was evaluated through organoleptic tests, pH, homogeneity, adhesion, melting point, and stability. Antioxidant activity was tested using the DPPH method with absorbance measurements using a UV-Vis spectrophotometer. The results showed that the green tea leaf eye stick preparation had good stability and antioxidant activity in F2 with an extract concentration of 6%, with an IC50 value of 57.2222 ppm, which is categorized as a strong antioxidant.